Filiaciones culturales y contactos entre las poblaciones Virú-Gallinazo y Mochica (200 AC-600 DC, costa norte del Perú) - Espinosa, Alicia, (Paris monographs in American archaeology ;, 2023)
This volume documents the pottery traditions to understand both their origins, filiations, and contacts, studying the modes of manufacture of archaeological ceramics discovered at more than nine sites in the region, preserved at the Ministry of Culture of Peru and various Peruvian, French and American museums.